IMPLEMENTASI METODE BERNYANYI SAMBIL BELAJAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENGINGAT TERHADAP MATERI KALIMAT TAYYIBAH PADA MATA PELAJARAN PAI KELAS III SD NEGRI SUKAHARJA II - Febrianto, Rahardi; Maulana, Raihan; Hanifah, Razita; Amani, Suci Jaoharoh; Zahrah, Windy Athira (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to examine the implementation of the "singing while learning" method in teaching Kalimat Thayyibah to third-grade students at SD Negeri Sukaharja II. Islamic Religious Education (PAI) at the elementary level plays a crucial role in instilling moral and spiritual values in students, particularly through materials such as Kalimat Thayyibah, which includes expressions like Bismillah, Alhamdulillah, and Subhanallah. However, many students find it difficult to read and memorize these phrases due to monotonous teaching methods. This research employs Classroom Action Research (CAR) conducted in two cycles, involving 44 students as research subjects. Data were collected through observation, tests, interviews, and documentation, and analyzed descriptively. The results showed a significant improvement in students’ learning outcomes. In the pre-cycle, only 27% of students achieved the minimum passing grade, while in the second cycle, 91% reached the target. The use of singing, combined with hand movements and group activities, increased student engagement, improved memory retention, and created a more enjoyable learning environment. Thus, the singing method proved effective in enhancing students' ability to read and memorize Kalimat Thayyibah in Islamic Religious Education lessons.